Single‐dose, placebo‐controlled, randomized study of AMG 785, a sclerostin monoclonal antibody - Padhi, Desmond; Jang, Graham; Stouch, Brian; Fang, Liang; Posvar, Edward (Journal of bone and mineral research, 2011)
Sclerostin, an osteocyte‐secreted protein, negatively regulates osteoblasts and inhibits bone formation. In this first‐in‐human study, a sclerostin monoclonal antibody (AMG 785) was administered to healthy men and postmenopausal women. In this phase I, randomized, double‐blind, placebo‐controlled, ascending, single‐dose study, 72 healthy subjects received AMG 785 or placebo (3:1) subcutaneously (0.1, 0.3, 1, 3, 5, or 10 mg/kg) or intravenously (1 or 5 mg/kg). Depending on dose, subjects were followed for up to 85 days. The effects of AMG 785 on safety and tolerability (primary objectives) and pharmacokinetics, bone turnover markers, and bone mineral density (secondary objectives) were evaluated. AMG 785 generally was well tolerated. One treatment‐related serious adverse event of nonspecific hepatitis was reported and was resolved. No deaths or study discontinuations occurred. AMG 785 pharmacokinetics were nonlinear with dose. Dose‐related increases in the bone‐formation markers procollagen type 1 N‐propeptide (P1NP), bone‐specific alkaline phosphatase (BAP), and osteocalcin were observed, along with a dose‐related decrease in the bone‐resorption marker serum C‐telopeptide (sCTx), resulting in a large anabolic window. In addition, statistically significant increases in bone mineral density of up to 5.3% at the lumbar spine and 2.8% at the total hip compared with placebo were observed on day 85. Six subjects in the higher‐dose groups developed anti‐AMG 785 antibodies, 2 of which were neutralizing, with no discernible effect on the pharmacokinetics or pharmacodynamics. In summary, single doses of AMG 785 generally were well tolerated, and the data support further clinical investigation of sclerostin inhibition as a potential therapeutic strategy for conditions that could benefit from increased bone formation. © 2011 American Society for Bone and Mineral Research.